2019
DOI: 10.3389/fphar.2019.00869
|View full text |Cite
|
Sign up to set email alerts
|

Gomisin M2 Inhibits Mast Cell-Mediated Allergic Inflammation via Attenuation of FcεRI-Mediated Lyn and Fyn Activation and Intracellular Calcium Levels

Abstract: Mast cells are effector cells that induce allergic inflammation by secreting inflammatory mediators. Gomisin M2 (G.M2) is a lignan isolated from Schisandra chinensis (Turcz). Baill. exhibiting anti-cancer activities. We aimed to investigate the anti-allergic effects and the underlying mechanism of G.M2 in mast cell–mediated allergic inflammation. For the in vitro study, we used mouse bone marrow–derived mast cells, RBL-2H3, and rat peritoneal mast cells. G.M2 inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Fc ε RI-mediated mast cell activation involves calcium influx [ 25 ]. The release of intracellular calcium leads to the degranulation of mast cells.…”
Section: Discussionmentioning
confidence: 99%
“…Fc ε RI-mediated mast cell activation involves calcium influx [ 25 ]. The release of intracellular calcium leads to the degranulation of mast cells.…”
Section: Discussionmentioning
confidence: 99%
“…To date, it has been reported that GM2 was isolated from the fruit of S. rubriflora had an anti-HIV replication effect on H9 lymphocytes in vitro [ 26 ]. In addition, we have previously reported that GM2 isolated from S. chinensis fruit inhibited acute inflammation caused by mast cell-mediated allergic inflammation [ 16 ]. In this study, we have defined the role of GM2 in the chronic inflammatory skin disease, in particular, AD.…”
Section: Discussionmentioning
confidence: 99%
“…The extracts of S. chinensis have active lignans, such as deoxyschisandrin, γ-schisandrin, and gomisin [ 14 , 15 ]. Among the lignans, gomisin M2 (GM2) has slightly greater antiallergic properties through the suppression of mast cell activation compared to the other lignans [ 16 ]. Although whole S. chinesis extracts have been reported to suppress AD [ 17 , 18 ], the biological and pharmacological activities of GM2 within S. chinesis extracts are not well characterized as chronic relapsing inflammatory skin disease, particularly AD.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, lignans, which function as antioxidants and play a role in plant defenses, and exhibit anti-inflammatory and antioxidant activities that can be utilized to treat skin diseases (16). Among the lignans, gomisin M2 (GM2) has shown antiallergic effects by inhibiting mast cell activation and the human immunodeficiency virus (17)(18)(19).…”
Section: Gomisin M2 Alleviates Psoriasis-like Skin Inflammation By Inhibiting Inflammatory Signaling Pathwaysmentioning
confidence: 99%
“…1A and S2A). Recently, GM2 has been demonstrated to have anti-allergic effects (17). Therefore, to investigate whether GM2 reduced the number of mast cells in IMQ-induced skin, toluidine blue-stained tissues were microscopically examined.…”
Section: Gm2 Inhibits Psoriasis-associated Characteristics In Anmentioning
confidence: 99%